KEBIJAKAN PENGGUNAAN TENAGA KERJA ASING DI KOTA DUMAI PADA TAHUN 2016-2018 - Nadia Dwi Hariyanto; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The use of freeing workers in Dumai City is a phenomenon tha greatly influences the running og government in Dumai City. With the geographical conditions of Dumai City. With the geographical conditions of Dumai City which is an intenational trade channel and also an advanced industrial city in Riau Province, so the strategic geographical conditions make the interest of foreign workers come to work in Dumai City. Therefore the use of foreign workers must be in accordance with statutory regulations. The use of foreign workers in accordance with a the legislation will have a good impact an the City of Dumai, the need for good government policies in the use of foreign workers so that not only certain parties who fell the benefits in the useof  foreign workers in Dumai City. This study aims to describe how the implementation of the use of foreign workers in Dumai City in 2016-2018. Location of research in Dumai City, especially in the Department of Employment and Transmigration in Dumai City and Immigration Class II in Dumai City. Furthermore, file collection techniques were carried aut by interview and documentation. The results of this study are the lack of supervision of the use of foreign workers in Dumai City so that there are still foreign workers employed in Dumai City who work as unskilled laborers, foreign workers in Dumai City is dude to the lack of correlation between the Department of Manpower and Transmigration with the Immigration Class II in Dumai City, the lack of resources on the use of foreign workers. On the other hand the use of foreign workers also has a positive impact that can increase the PAD of Dumai City, transfet of knowledge and technology to local workers, also changes in work culture that has a positive impact and increase investment resulting in the economy in the City of Dumai as well increased. Actors involved in the use of foreign workers have met such as the presence of Immigration, the Department of Labor and Transmigration, the pora team, and Department of Population and Civil Registration. The existence of environmental support fo the use of foreign workers. A case of economic support thet is investors, political support that is mass organizations and social support one of which is the community. Keyword: Usage, Foreign Workers, Supervision, Actors, Enviromental Support